2006
DOI: 10.11606/issn.2316-9079.v5i2p119-133
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes of eight species of Leptodactylus (Anura, Leptodactylidae) with a description of a new karyotype for the genus

Abstract: Karyotypes of eight species of Leptodactylus (Anura, Leptodactylidae) with a description of a new karyotype for the genus. Eight species of the Neotropical genus Leptodactylus were karyologically studied:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
3
15
2
1
Order By: Relevance
“…However, an explanation for differences among species in their susceptibility to molecular reorganization of rDNA clusters is still lacking. Results of the present study contrast with the major pattern of only one chromosome pair with NOR that is found in the other Phyllomedusa and related species studied so far; however, multiple NORs have been described in several other anuran species (e.g., Wiley et al, 1989;Lourenço et al, 1998Lourenço et al, , 2000Veiga-Menoncello et al, 2003;Amaro-Ghilardi et al, 2006;Silva et al, 1999, indicating that this variation is common in this group.…”
Section: Discussioncontrasting
confidence: 99%
“…However, an explanation for differences among species in their susceptibility to molecular reorganization of rDNA clusters is still lacking. Results of the present study contrast with the major pattern of only one chromosome pair with NOR that is found in the other Phyllomedusa and related species studied so far; however, multiple NORs have been described in several other anuran species (e.g., Wiley et al, 1989;Lourenço et al, 1998Lourenço et al, , 2000Veiga-Menoncello et al, 2003;Amaro-Ghilardi et al, 2006;Silva et al, 1999, indicating that this variation is common in this group.…”
Section: Discussioncontrasting
confidence: 99%
“…Such differences in the quantity and distribution of the heterochromatin have been important for the definition of speciesand subspecies-level differentiation in amphibians (Matsui et al 1985). The heterochromatin distribution pattern observed in the specimens of L. latrans from Tobias Barreto was similar to that described by Amaro-Ghilardi et al (2006) in specimens from Igarassu (Pernambuco, Brazil), which presented C-positive pericentromeric blocs on the short arms of chromosomes 4, 7 and 8.…”
Section: Discussionsupporting
confidence: 55%
“…While both the species analyzed in the present study had been previously karyotyped, beginning in the 1970s (Denaro 1972, Bianchi et al 1973, Bogart 1974, and revised more recently (Amaro- Ghilardi et al 2006, Silva et al 2006, this is the first cytogenetic study of populations from the Caatinga, the least well protected Brazilian biome (Leal et al 2005).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite differences in position, the occurrence of a secondary constriction on chromosome 8, carrier of the NORs in species of Leptodactylus was referred to by Baldo (2002) and Amaro-Ghilardi et al (2006). In the present study, only on chromosome 8 of L. labyrinthicus was the secondary constriction not observed, probably due to differences in the degree of chromosome condensation in preparations.…”
Section: Cytogenetic Analysiscontrasting
confidence: 46%